Advanced Pulmonary Sarcoidosis - Gupta, Rohit; Baughman, Robert P. (Seminars in Respiratory and Critical Care Medicine, 2020)
At least 5% of sarcoidosis patients die from their disease, usually from advanced pulmonary sarcoidosis. The three major problems encountered in advanced pulmonary sarcoidosis are pulmonary fibrosis, pulmonary hypertension, and respiratory infections. Pulmonary fibrosis is the result of chronic inflammation, but other factors including abnormal wound healing may be important. Sarcoidosis-associated pulmonary hypertension (SAPH) is multifactorial including parenchymal fibrosis, vascular granulomas, and hypoxia. Respiratory infections can be cause by structural changes in the lung and impaired immunity due to sarcoidosis or therapy. Anti-inflammatory therapy alone is not effective in most forms of advanced pulmonary sarcoidosis. New techniques, including high-resolution computer tomography and 18F-fluorodeoxyglucose positron emission tomography (PET) have proved helpful in identifying the cause of advanced disease and directing specific therapy.
Keywords: pulmonary fibrosis; pulmonary hypertension; mortality; bronchiectasis; fungal infections